Cleaning-up Bank Balance Sheets : Economic, Legal, and Supervisory Measures for Italy - Garrido, Jose (IMF Working Papers; Working Paper ;, 2016)
To stabilize and bring down nonperforming loans (NPLs) in the Italian banking system, the Italian authorities have been implementing a number of reforms, aimed among others at speeding up insolvency and enforcement proceedings, strengthening bank corporate governance, cleaning up balance sheets, and facilitating bank consolidation. This paper examines the Italian banking system's NPL problem, which ties up capital, weighing on bank profitability and authorities' economic reforms. It argues for a comprehensive approach, encompassing economic, supervisory, and legal measures. The authorities' reforms are important steps toward this end. The paper describes measures that could further support their actions.